Experimental characterization and modeling of microwave heating of oil palm kernels, mesocarps, and empty fruit bunches - Law, Ming; Chang, J.; Chan, Stephanie; Pui, D.; You, K. (Taylor and Francis Inc, 2018)
The current work investigates the microwave heating and drying behavior of oil palm fresh fruits and bunches. Dielectric, thermal, and mechanical properties of oil palm kernels (OPKs), mesocarps, and empty fruit bunches (EFBs) were determined. New empirical models of the dielectric constant, loss factor, elastic modulus, and yield stress as functions of moisture content were obtained for OPKs, mesocarps, and EFBs. The thermal conductivity of the mesocarps and EFBs was 0.458 and 0.0285?W/(m K), respectively. Thermal analyses showed that decomposition of OPKs, mesocarps, and EFBs started when the temperature exceeded 100°C. Multiphysics models that consider electromagnetic waves, moisture, and heat conservation as well as material deformation were developed for OPKs, mesocarps, and EFBs. The simulation results show that an EFB sample with high moisture content generated a high moisture gradient during heating, causing high stress that exceeded its yield stress. However, this effect occurred only during the initial heating. Our results show that microwave heating can aid the detachment of oil palm fruit from bunches before EFBs harden because of moisture loss.